Rancang Bangun Alat Pengering Tepung Terubuk Otomatis berbasis Arduino Uno - Yusup, Muhammad; Astuti, Irnin Agustina Dwi (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2023)
The terubuk plant is widely found in the Tegalwaru District of Karawang Regency, which is known for its high nutritional and vitamin content. Terubuk is usually only utilized by the local community as a vegetable. To process it into other food products, production tools are needed for managing terubuk, one of which is a drying machine. The purpose of this research is to design and construct a terubuk drying machine based on an Arduino microcontroller. The required tools and materials include iron, steel, heating elements, burners, blowers, air ducts, thermostats, hygrometers, stainless steel racks, Arduino Uno, female-to-female cables, temperature sensors, humidity sensors, relays, power supplies, and nails. The Arduino microcontroller-based terubuk flour drying machine is an innovative production tool designed to facilitate the drying of terubuk and reduce its moisture content, making it easier to process into terubuk flour in the future.